Utilities and industrial history
1 online resource.
Keywords: "This shortform book presents key peer-reviewed research selected by expert series editors and contextualised by new analysis on the industrial history of delivering utilities. With contributions on the strengths and weaknesses of the creation of electricity networks, the organisation and performance of Britain's nationalised gas industry, and the environmental impact of delivering water and removing waste water, this volume provides an array of fascinating insights into industrial history. Of interest to business and economic historians, this shortform book also provides analysis and illustrative case-studies that will be valuable reading across the social sciences"--